Eksaminasi publik sebagai instrumen kontrol sosial terhadap putusan pengadilan - ma'ruf, amar (Maliki Interdisciplinary Journal, 2026)
Public examination is a form of community participation in supervising judicial power through critical reviews of court decisions. In Indonesia, this practice has developed as a response to weak internal oversight mechanisms, particularly regarding controversial rulings or decisions suspected of reflecting injustice. This article discusses public examination as an instrument of social control involving civil society organizations, academics, and legal practitioners to assess legal reasoning, judicial considerations, and fairness in court judgments. Using a normative juridical approach, the study highlights the urgency of strengthening public examination and proposes a writing framework that may serve as practical guidance. Beyond its corrective role, public examination is also educational because it improves public understanding of the legal reasoning applied by judges. This practice has frequently been used in major cases, especially corruption and high-impact disputes, demonstrating its relevance in a democratic legal system. Public examination has proven capable of promoting judicial accountability, improving the quality of decisions, enhancing transparency, and strengthening public trust in the judiciary through greater integrity and institutional support.